CYTOTOXIC EFFECT OF FREEZE DRIED BOVINE CARTILAGE POWDER AND PLATELET RICH PLASMA (PRP) TO MESENCHYMAL STEM CELL (MSCs) - Dwikora Novembri Utomo; Anthoni Yusbida (Journal Orthopaedi and Traumatology Surabaya, 2017)
Cartilage repair is a challenging clinical problem because the damage is an irreversible condition. Many studies had been performed using several kinds of natural or synthetic scaffold. Attempts to repair articular cartilage using scaffold usually found many problems, lacks the physical structure and mechanical properties necessary to ensure long-term efficacy to cartilage defect. Furthermore, scaffold frequently cause toxicity to the host. Therefore, this study was performed in vitro to test the toxicity effect of scaffold freeze dried bovine cartilage powder and platelets Rich Plasma (PRP). This research was conducted using pure experimental research design in 4 groups of animal stem cells which being added with scaffold freeze dried bovine cartilage scaffold provided with platelet rich plasma. This study using posttest only control group design. The result being processed with MTT assay and spectrophotometer for counting the viable stem cells. There was no significant difference in the amount of macrophage between control and the freeze dried bovine cartilage scaffold provided with PRP (p=0,128). With this result in the number of macrophages between the control with freeze dried bovine cartilage scaffold provided PRP, it can be concluded that these biomaterials have biocompatibility.